Bangladesh : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 2000)
Recent economic and financial developments in Bangladesh were greatly marked by massive floods. Fiscal and monetary policies have been adopted under the government's emergency flood assistance program, with a view to funding relief and rehabilitation measures without undermining macroeconomic stability. Output growth is estimated to have declined. The overall fiscal deficit has widened and the monetary policy has been more expansionary than programmed. The government has taken important steps to improve the regulatory and legal environment for banks. External sector developments have been greatly affected.